2020
DOI: 10.1108/dat-03-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelic substance use in the Reddit psychonaut community. A qualitative study on motives and modalities

Abstract: Purpose The purpose of this paper is to investigate motives and modalities of psychedelic substance use in the psychonaut community that is hosted on the Reddit platform (r/psychonaut). Psychonauts are sometimes described as responsible drug users. Elements of responsible use include sharing stories, advice and experiences, reagent testing substances, proper dosing and education on harm reduction and its practical implication. Investigating psychonauts’ substance use can highlight what responsible use means fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Reddit is an online social network, news aggregator, and host of forums for communities with common interests to share, discuss, and comment on a topic 45 , 46 . Data from Reddit has been aggregated previously to inform peer-reviewed research 46 48 . The r/DMT community is a public forum for the discussion and sharing of information pertaining to DMT and is a rich community-based open-access resource, which includes individuals reporting and describing DMT experiences.…”
Section: Methodsmentioning
confidence: 99%
“…Reddit is an online social network, news aggregator, and host of forums for communities with common interests to share, discuss, and comment on a topic 45 , 46 . Data from Reddit has been aggregated previously to inform peer-reviewed research 46 48 . The r/DMT community is a public forum for the discussion and sharing of information pertaining to DMT and is a rich community-based open-access resource, which includes individuals reporting and describing DMT experiences.…”
Section: Methodsmentioning
confidence: 99%
“…While research has stalled for decades due to the legal status of psychedelic drugs, public interest has not. Psychedelic self-medication has grown in popularity in recent years, reportedly making up 14.8% of self-reported psychedelic substance use ( 74 ) and first time LSD-use having increased ten-fold in 10 years in adults over 26 ( 75 ). Methods of use range from the semi-regular taking of sub-perceptible doses (known as “microdosing”) to isolated high dose sessions emulating clinical contexts to address mental health concerns ( 76 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of punishing outright the 35 million adults in the United States who have used classic psychedelics, organizations could benefit by understanding why applicants used these substances. In a recent study of an online forum for psychedelic users, roughly 17% of users indicated the stimulation of artistic creativity/performance as a motive for their psychedelic use (Pestana, Beccaria, & Petrilli, 2020). In another study, 17% of psychedelic users reported using psychedelics to help them work or study (Kettner, Mason, & Kuypers, 2019).…”
Section: Discussionmentioning
confidence: 99%